Kinetic and Equilibrium Modeling of Lead(II) Sorption onto Chemically Pretreated Gossypium hirsutum (Cotton) Leaves Waste Biomass - Riaz, Muhammad; Nadeem, Raziya; Asif Hanif, Muhammad; Rasool, Nasir; Saeed, Rashid; Idrees Jilani, Muhammad; Iqbal, Tahira; Zafar, Muddassar (Asian Journal of Chemistry, 2012)
Equilibrium and kinetic aspect of lead(II) biosorption onto chemically pretreated G. hirsutum (cotton) leaves waste biomass was investigated in the present study. The lead(II) sorption was found dependent on solution pH, initial lead(II) concentration, temperature and contact time. The chemical pretreatment of biomass resulted in significant enhancement and reduction in sorption capacity depending on the nature of pretreatment. Results revealed that chemical modifications of G. hirsutum (cotton) leaves waste biomass with alkali, inorganic salts, organic salts and organic solvents enhanced the adsorption capacity, while acidic pretreatments caused reduction in adsorption capacity. The sorption data was fitted well to Langmuir isotherm and kinetic data to pseudo second order model, due to higher value of correlation coefficient (R2). The effect of contact time showed that sorption of lead(II) occurred rapidly within first 0.5 h followed by slow adsorption till equili-brium. Present research work illustrated an effective and economical biosorbent for the removal of toxic heavy metals from aqueous solutions.